2004
DOI: 10.1890/02-5353
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Biological Control: The Population Regulation of Nezara Viridula by Trichopoda Giacomellii

Abstract: The role of the aggregated distribution of attacks, a castration effect (cessation of reproduction of the parasitized hosts) and the differential selectivity for hosts by the parasitoid Trichopoda giacomellii on the population regulation of its host, Nezara viridula, was investigated using a detail‐rich simulation model. The model parameters were estimated either in the laboratory or under field conditions. Additionally, key parameter values were estimated by fitting the model to field data of nine generations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…These models combine small-scale observations or experiments for measuring process rates with field measurements of spatial variability. This approach has a long history in the study of host-parasitoid interactions, where models originally developed by Bailey et al (1962) and May (1978) have been used to examine the dynamic consequences of heterogeneity in the distribution of parasitoid attacks (e.g., Hassell 1980;Jones et al 1993;Liljesthröm and Rabinovich 2004). A similar approach has been used in studies of host-parasite interactions (Dobson and Hudson 1992;Barlow 2000).…”
mentioning
confidence: 99%
“…These models combine small-scale observations or experiments for measuring process rates with field measurements of spatial variability. This approach has a long history in the study of host-parasitoid interactions, where models originally developed by Bailey et al (1962) and May (1978) have been used to examine the dynamic consequences of heterogeneity in the distribution of parasitoid attacks (e.g., Hassell 1980;Jones et al 1993;Liljesthröm and Rabinovich 2004). A similar approach has been used in studies of host-parasite interactions (Dobson and Hudson 1992;Barlow 2000).…”
mentioning
confidence: 99%
“…We assume the latter to be a plausible explanation because the third generation of N. viridula adults (in pre-reproductive stage) leaves the feeding/reproducing area in search for hibernating shelters (in our study area the hibernation period lasts approximately 5 months of the colder period of the year). N. viridula individuals leaving hibernation re-colonize the area in the following spring and reproduce, originating the first new generation of eggs (Liljesthröm & Bernstein, 1990; Liljesthröm & Rabinovich, 2004). T. basalis also hibernates in the adult stage, and Doetzer & Foerster (2007) estimated that adult winter survivorship proportion in Brazil was 0.85 and decreased in spring; however, little is known about T. basalis adult dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…In order to have a representative sample of the conditions of the field population, the 100 pairs of adult hosts were substituted by others taken from the field each time a 15–20% increase in N. viridula parasitism by T richopoda giacomellii (Blanchard) (Diptera: Tachinidae) was registered in the field. This parasitoid attacks older nymphs and young adults and its effect is a reduction in host fecundity without affecting host egg fertility (Liljesthröm, 1983; Liljesthröm & Rabinovich, 2004). Adult N. viridula density in the field was estimated by counting the total number in 30 1 m 2 -square units distributed at random in the area (for more details see Liljesthröm & Bernstein, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Rather, several tachinid species already present in areas invaded by N. viridula formed new associations with the pest when it invaded North America ( Trichopoda pennipes ), South America ( Trichopoda giacomellii ) and the West Indies ( Trichopoda pilipes ). In most cases, these tachinids now attack N. viridula more commonly than their presumed native hosts in these areas, and parasitism levels at some points in the season can be very high (>40%) . In Argentina there were long‐term and detailed studies conducted on the impact of T. giacomellii on N. viridula populations over >20 generations of the insects .…”
Section: Past Biological Control Programs Against Invasive Stink Bugsmentioning
confidence: 99%
“…In most cases, these tachinids now attack N. viridula more commonly than their presumed native hosts in these areas, and parasitism levels at some points in the season can be very high (>40%) . In Argentina there were long‐term and detailed studies conducted on the impact of T. giacomellii on N. viridula populations over >20 generations of the insects . Key‐factor analysis of these data suggested that T. giacomellii , via density‐dependent parasitism of N. viridula , contributed strongly to regulation of stink bug population levels, in combination with nymph mortality from predation and abiotic factors and egg parasitism by T. basalis .…”
Section: Past Biological Control Programs Against Invasive Stink Bugsmentioning
confidence: 99%